The Routledge Handbook of EU-Africa Relations - Mah, L.; Haastrup, T.; Duggan, N. (2020)
This handbook provides a comprehensive overview of the changing dynamics in the relationship between the African continent and the EU, provided by leading experts in the field. Structured into five parts, the handbook provides an incisive look at the past, present and potential futures of EU-Africa relations. The cutting-edge chapters cover themes like multilateralism, development assistance, institutions, gender equality and science and technology, among others. Thoroughly researched, this book provides original reflections from a diversity of conceptual and theoretical perspectives, from experts in Africa, Europe and beyond. The handbook thus offers rich and comprehensive analyses of contemporary global politics as manifested in Africa and Europe. The Routledge Handbook of EU-Africa Relations will be an essential reference for scholars, students, researchers, policy makers and practitioners interested and working in a range of fields within the (sub)disciplines of African and EU studies, European politics and international studies. The Routledge Handbook of EU-Africa Relations is part of the mini-series Europe in the World Handbooks examining EU-regional relations and established by Professor Wei Shen.